Implementasi Semangat Kerjasama Untuk Meningkatkan Kepedulian Sosial di Masyarakat Banjar: Implementing the Spirit of Cooperation to Enhance Social Awareness in the Banjar Community - Normalasarie, Normalasarie (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
The Banjar community is known for its spirit of cooperation, demonstrated through mutual assistance and solidarity in various social and cultural activities. This research aims to explore and analyze the implementation of cooperative spirit in enhancing social awareness within the Banjar community. Banjar community is renowned for its strong culture of mutual aid, the challengers of modernization and social change may affect these values. This study uses a mixed-method approach, combining qualitative and quantitative data to measure and understand the level of cooperation among the Banjar people. Qualitative data were collected through in-depth interviews and participatory observations, while quantitative data were obtained through surveys and structured questionnaires that assess the dimension of cooperative and social awareness. Study results indicate that cooperative activities, such as mutual assistance and communal religious gatherings, can strengthen social network and enhance social awareness among community members. However, the study also identified challenges, such as individualism and social inequality, which need to be addressed to maximize the positive impact of cooperation. This study recommends the implementation of more innovative strategies to promote cooperation and strengthen social awareness in the Banjar community.